2020
DOI: 10.3390/ma13245668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reactive SPS on the Microstructure and Properties of a Dual-Phase Ni-Al Intermetallic Compound and Ni-Al-TiB2 Composite

Abstract: As part of the tests, a two-phase NiAl/Ni3Al alloy and a composite based on this alloy with 4 vol% addition of TiB2 were produced by the reactive FAST/SPS (Field Assisted Sintering Technology/Spark Plasma Sintering) sintering method. The sintering process was carried out at 1273 K for 30 s under an argon atmosphere. The effect of reactive SPS on the density, microstructure, and mechanical and tribological properties of a dual-phase Ni-Al intermetallic compound and Ni-Al-TiB2 composite was investigated. Product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…This was pointed out by Thompson et al [77], who described the effect of alloy addition on the microstructure evolution in Ni-Al alloys. The same was also observed by the author in his own research [33], where the introduced ceramic particles were found to have an effect on the composite microstructure formed as a result of combustion synthesis (CS). Ozdemir [78] obtained an almost identical microstructure of the two-phase NiAl-Ni 3 Al alloy with a molar ratio of Ni and Al equal to 13:7.…”
Section: Microstructural Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…This was pointed out by Thompson et al [77], who described the effect of alloy addition on the microstructure evolution in Ni-Al alloys. The same was also observed by the author in his own research [33], where the introduced ceramic particles were found to have an effect on the composite microstructure formed as a result of combustion synthesis (CS). Ozdemir [78] obtained an almost identical microstructure of the two-phase NiAl-Ni 3 Al alloy with a molar ratio of Ni and Al equal to 13:7.…”
Section: Microstructural Analysissupporting
confidence: 74%
“…Special attention in the manufacture of Ni-Al Materials 2023, 16,1907 2 of 21 alloys deserves the technology of powder metallurgy as an important tool that allows abating the adverse effect of brittleness [2] through the use of various manufacturing methods [20,21], microstructure optimization [22,23] or ultra-fine grain refinement [24]. Numerous variations of the sintering process have been used to meet this goal, starting with free sintering [25,26], through the techniques that use both high sintering temperatures (HP-hot pressing, HIP-hot isostatic pressing) [22,27,28] and high sintering pressure (HPHT-high pressure high temperature) [29,30], and ending in the methods where thermal effects are obtained by the use of direct current, alternating current or pulsed current (SPS-spark plasma sintering) [31][32][33]. Currently, scientists are particularly interested in the SPS method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NiAl can be produced by several methods, such as casting, mechanical alloying [8], spark plasma sintering (SPS) [3,9], dynamic powder compaction [10], and powder metallurgy [11]. Most of the above methods require complex and expensive equipment and are time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods of NiAl manufacturing such as casting, mechanical alloying [2,4], spark plasma sintering (SPS) [5], dynamic powder compaction (DPC) [6], and powder metallurgy [7]. Combustion synthesis (CS), which is a type of powder metallurgy, is a relatively rapid energy-efficient process of NiAl manufacturing, which does not require any special equipment [8,9].…”
Section: Introductionmentioning
confidence: 99%